PENERAPAN DESENTRALISASI FISKAL DI NEGARA CINA DAN NEGARA INDONESIA - Wijaya, I Made Hendra (Jurnal Advokasi, 2016)
These days economic and financial sector is to determine the progress of a country around the world, in the country of China began to implement the concept of fiscal decentralization to improve the economy and its financial sector after the economic reforms in the 2000s. In Indonesia itself, fiscal decentralization began attending since the fall of the New Order era, namely the beginning of the reform era, with the exclusion of some Act to reinforce the concept of fiscal decentralization in the country of Indonesia. Fiscal decentralization is part of the reform measures around the world, the concept of fiscal decentralization is devolution from central government to local government in the conduct of economic and financial management.